Attitudes of Support Staff Towards People with Intellectual Disabilities Under Their Care: A Systematic Review of Literature - Anis Maria; Nordin Nor Akmar (Insight: the psychological dimensions of society, 2024)
Purpose. Current literature on attitudes of support staff towards people with intellectual disabilities produces heterogenous findings. The present systematic review aims to provide a synthesis and thorough appraisal of qualitative and quantitative evidence on attitudes of support staff towards people with intellectual disabilities under their care. Methods. A systematic literature search was performed across four electronic databases to identify original articles published in English between 2014 and 2024. PICO framework and PRISMA statement were used to organize the search strategy and study selection. The references were screened on predefined inclusion and exclusion criteria which resulted in 38 studies being included in the review. Results. Four themes emerged: 1) attitudes towards integration and participation, 2) attitudes towards autonomous decision-making, 3) attitudes towards sexual needs and sexual expression, and 4) attitudes towards restrictive measures and restraint interventions. Findings suggest that support staff held skeptical attitudes concerning integration and meaningful participation of people with intellectual disabilities. Moreover, support staff operated under the premise that people with intellectual disabilities were not capable of making independent decisions because they did not understand the consequences of their choices. Support staff considered sexual expression of people with intellectual disabilities a human right, but they expressed insecurity concerning the matter and approached certain facets of sexual expression with caution. Lastly, support staff were clear and unequivocal when it came to the use of restraint and restrictive measures insisting that they used them to regulate the behaviors of people with intellectual disabilities which might harm them or others. Discussion and Conclusions. Variations in attitudes are evident as some support staff exhibit a sincere regard for the welfare and potential of people with intellectual disabilities while others harbor biases towards them. The findings stress the need to address these varied attitudes to enable support staff in delivering high-quality care and support to people with intellectual disabilities.